English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

a. l = P - w

b. l = (P - w) / 2

c. l = (P - 2w) / 2

d. l = P - 2w

2007-03-12 05:22:20 · 2 answers · asked by Anonymous in Science & Mathematics Mathematics

2 answers

The answer is c.

2007-03-12 06:01:18 · answer #1 · answered by MHW 5 · 0 0

2l+2w=P
2l=P-2w
l=(P-2w)/2
therefore c is correct

2007-03-12 13:07:25 · answer #2 · answered by alpha 7 · 0 0

fedest.com, questions and answers